Comparative metagenomics of hydrocarbon and methane seeps of the Gulf of Mexico. Issue 1 (December 2017) - Vigneron, Adrien; Alsop, Eric; Cruaud, Perrine; Philibert, Gwenaelle; King, Benjamin; Baksmaty, Leslie; Lavallée, David; Lomans, Bartholomeus; Kyrpides, Nikos; Head, Ian; Tsesmetzis, Nicolas
Abstract Oil and gas percolate profusely through the sediments of the Gulf of Mexico, leading to numerous seeps at the seafloor, where complex microbial, and sometimes animal communities flourish. Sediments from three areas (two cold seeps with contrasting hydrocarbon composition and a site outside any area of active seepage) of the Gulf of Mexico were investigated and compared. Consistent with the existence of a seep microbiome, a distinct microbial community was observed in seep areas compared to sediment from outside areas of active seepage. The microbial community from sediments without any influence from hydrocarbon seepage was characterized byPlanctomycetes and the metabolic potential was consistent with detrital marine snow degradation. By contrast, in seep samples with methane as the principal hydrocarbon, methane oxidation by abundant members of ANME-1 was likely the predominant process. Seep samples characterized by fluids containing both methane and complex hydrocarbons, were characterized by abundantChloroflexi (Anaerolinaceae ) and deltaproteobacterial lineages and exhibited potential for complex hydrocarbon degradation. These different metabolic capacities suggested that microorganisms in cold seeps can potentially rely on other processes beyond methane oxidation and that the hydrocarbon composition of the seep fluids may be a critical factor structuring the seafloor microbial community composition and function.